FRET (fluorescence resonance energy transfer) sheds light on transcription. (19th January 2011) - Grohmann, Dina; Klose, Daniel; Fielden, Daniel; Werner, Finn
Abstract : The complex organization of the transcription machinery has been revealed mainly by biochemical and crystallographic studies. X-ray structures describe RNA polymerases and transcription complexes on an atomic level, but fail to portray their dynamic nature. The use of fluorescence techniques has made it possible to add a new layer of information to our understanding of transcription by providing details about the structural rearrangement of mobile elements and the network of interactions within transcription complexes in solution and in real-time.